THE ROLE OF DUALITY MANAGERIAL OWNERSHIP AND BOARDS ON IPO VALUE (AN EMPIRICAL EVIDENCE OF INDONESIAN FIRMS) - Maximus Leonardo Taolin; Julia Safitri (Jurnal Penelitian Ekonomi dan Bisnis, 2020)
The research aims to find the impact of ownership retention, managerial ownership, and boards on value IPO premium and underpricing. We investigate by using hand collect data 202 IPO prospectuses during 2008-2017 and using Warp PLS 5.0 to compute the data. Our finding suggests that may use to guide the investor in making informed decisions to see the level of the proportion of sharehold by old ownership and management. When the high level of ownership retention and managerial ownership, make the value IPO premium and underpricing will be high. On the other hand duality of the managerial role in firms making the value will be achieved. This paper contributes to the value of IPO premium and underpricing literature when influence by ownership share on initial public offerings  context of emerging markets.Keywords: Ownership retention; Managerial Ownership; Boards; IPO premium; underpricing